Japanese management and salary productivity : the case of the electronic and automotive industries in Portugal - Silva, Victor Paulo Gomes da (2010)
The present paper intended to assert in what form the Japanese approach to business management, concerning the factors human resources, research and development and organization and methods, has effect on the value creation by workers, beyond those expressed in salaries. The investigation fell on companies in the electronic and automotive sectors operating in Portugal, with and without Japanese capital, in the six-year span from 2001 to 2006. The specific results demonstrated that that impact is clearly visible over the factor organization and methods. In addition, there are evidences of substantial and direct influence of research and development on the creation of surplus value.